Southerly portion Vancouver Island - Hutchinson, W. H. (ctg) (British Columbia Department of Lands and Forests, 1951)
This is a map of Southern Vancouver Island in 1951 showing alienated and covered by applications under the Land Act lands, surveyed timber lease lands, First Nations and government reserves, forests, parks, roads, railways, power lines, trails, cities and towns. "Map No. 2A" Scale 1:253,440, or 4 miles to 1 inch. Relief shown by spot heights. Shows alienated and covered by applications under the Land Act lands, surveyed timber lease lands, lots distribution, First Nations and government reserves, forests, parks, roads, railways, power lines, trails, cities and towns. Lots numbered. Includes regional map, road mileage tables, and nauical mile distances from Vancouver to major international cities. Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ .